Work adjustment of middle-aged Korean women and its implications for policy. (2017) - Lee, Young-Min; Choi, Young-Sup; Lim, Jung-Yon
The purpose of this research was to gain an understanding of the (re-)employment situation of middle-aged women in Korea, and to make suggestions for adapting their work environment. Regardless of past work experience, middle-aged Korean women who are newly employed or re-enter the labour market after a substantive period of career discontinuity are facing difficulty adapting to the organisational culture of the new jobs, and achieving work performance. For the analysis, a survey was conducted on job-seeking women recruited through regional employment centres across the country. Selections of 356 surveys were analysed using SPSS 18.0. It was found that middle-aged women in the workplace can face a variety of conflict situations. Among the conflicts, personal relation conflicts with co-workers were found to be the most commonly observable maladjustment behaviour, compared to other kinds of maladjustment activities that are mainly caused by lack of job-specific skills. The main reason for the various kinds of maladjustment was correlated with inappropriate management of the company system. Such maladjustment situations are also clearly increasing the intentions of middle-aged women to quit their current job, or furthermore, to (re-)exit from the labour market.